Health-related quality of life among hepatitis c patients in Pahang State, Malaysia: a cross-sectional study - Zainulabid, Ummu Afeera; Md Jalil, Muhammad Ateeq; Jaafar, Khairul Azhar; Ahmad, Hajar Fauzan; Mohd Ibrahim, Mohamad Shafiq; M Yunus, Raudah (PERINTIS eJournal, 2021)
Measurement of health-related quality of life (HRQOL) among hepatitis C patients is crucial in assisting health care providers to understand the complex psychosocial impact of disease on patients, thus facilitating a more patient-centred care. There is still scarcity of data on this matter, not adequately explored and nor has it been empirically studied in Malaysia. Thus, this study aims to measure the HRQOL among hepatitis C patients attending a tertiary hospital in Pahang, Malaysia. This was a cross-sectional study conducted among 195 hepatitis C patients attending Hospital Tengku Ampuan Afzan (HTAA), the main public tertiary hospital in Pahang. HRQOL was assessed using the 36-item short-form survey (SF-36v2). Respondents had lower scores in physical (mean score = 48.88 ± 8.9) and mental (mean score = 47.70 ± 9.1) health components of HRQOL than normal population (mean score > 50). Those who completed treatment had higher scores in both physical and mental health component, compared to those who was not treated or on treatment. There was no significant association between HRQOL and gender, age, marital status, employment status and education level. Our findings showed that patients with hepatitis C, in general, have poor HRQOL in both physical and mental health components. Thus, this study highlights a pressing need for holistic disease management by taking into account patients’ quality of life as part of the inter-disciplinary approach.